2020
DOI: 10.1590/0034-7167-2017-0919
|View full text |Cite
|
Sign up to set email alerts
|

Nursing work in assisted human reproduction: between technology and humanization

Abstract: Objectives: To analyze the social representations of nurses who work with assisted human reproduction about the operation with reproductive biotechnologies. Methods: Qualitative approach, supported by the Theory of Social Representations, with sixteen participants. Individual, semi-structured interviews, analyzed through the Alceste software. Results: Pragmatic elements related to nurses’ performance from a professional, institutional, and public policy perspective in reproductive biotechnologies emerged, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
5
0
4
Order By: Relevance
“…Based on the logic that AHR is part of the future when it comes to human reproduction for couples with infertility, this segment, unlike the previous one, understands that reproductive biotechnology is a promising field of work for nurses, according to Class 2. These highlight the need to be highly specialized and differentiated professionals, since they must articulate technological knowledge, welcoming and ethics (7,18) . This inference may be based on some international research on the role of nurses in AHR, such as a study carried out in the United States (2018) on a new strategy that is being used by nurses in this field, which is Telenursing, used to communicate with patients on fertility and reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the logic that AHR is part of the future when it comes to human reproduction for couples with infertility, this segment, unlike the previous one, understands that reproductive biotechnology is a promising field of work for nurses, according to Class 2. These highlight the need to be highly specialized and differentiated professionals, since they must articulate technological knowledge, welcoming and ethics (7,18) . This inference may be based on some international research on the role of nurses in AHR, such as a study carried out in the United States (2018) on a new strategy that is being used by nurses in this field, which is Telenursing, used to communicate with patients on fertility and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…The progress of technological interventions in the process of human procreation requires greater training of professionals for skills in different fields of this knowledge, due to the bioethical, social and religious implications (5)(6) . In this idea, it is observed that conversations, concerns, opinions and decision-making about reproductive biotechnologies are raised by sexual and reproductive health (SRH) nurses, which, in turn, influence professional practice to that kind of reproduction (7) .…”
Section: Introductionmentioning
confidence: 99%
“…As situações críticas apontadas pelas participantes, fundamentam-se no apoio emocional oferecido aos pais, com o intuito de proporcionar um ambiente acolhedor, disponibilizar suporte relacional, como orientar e fornecer as informações clínicas consistentes e, incentivar o contato pele a pele. Essas tecnologias leves têm sido utilizadas para mediar o vínculo dos pais desses prematuros a lidar com a ansiedade inerente à condição de ter um bebê internado na UTIN e facilitar o acesso às redes de apoio (Sousa et al, 2017;Balbino et al, 2015;Queiroz et al, 2020) Para as participantes, são inúmeras as situações de cuidado ao bebê e sua família na UTIN, assim como o modo de organização das informações adquiridas que coadunam o conjunto de valores, crenças, expectativas e necessidades individuais e coletivas, que lhe permitem ações complexas, envolvendo aspectos cognitivos, comportamentais, afetivos-emocionais e intencionais, balizados por meio de relações estabelecidas que proporcionam a aquisição informações assertivas para interação do cuidado (Balbino et al, 2015;Al Maghaireh et al, 2016;Facio et al, 2016;Queiroz et al, 2020).…”
Section: Discussionunclassified
“…Regarding this component, it is also mentioned that studies reiterate challenges to be overcome for the effective implementation of such actions, such as the scarcity of educational activities for SRH care; approach centered on the figure of the woman; content often limited to sexually transmitted infections; difficulty of adherence and participation of users in educational activities; need for welcoming and preconception care; absence of counseling and/or moments of dialogue with users who seek such assistance, and prescriptive conduct of professionals (2,(14)(15)(16)(17) .…”
Section: Actionmentioning
confidence: 99%
“…Articulation with other services and definition of strategies for carrying out health information and surveillance activities. Although scarce, studies already done show that inadequate physical spaces, lack of supplies, lack of trained human resources, work overload, fragmentation of care, moral and religious precepts, lack of communication in the care network and precariousness of physical facilities and working conditions are issues that directly influence the supply and quality of promotion activities and clinical care of SRH care in the context of primary care (4,11,(15)(16)(17) . These and other aspects, therefore, need to be considered in the context of public health and deepened in the scope of the construction of theoretical models, analysis, and evaluation of public policies.…”
Section: Theoretical Model -Clinical Care Component For Sexual and Re...mentioning
confidence: 99%